Psychological Contribution, Disciplined Behavior, and Driving Compensation to Safety with Satisfaction Job As an Intervening Variable (Community Engagement and Emergence Journal (CEEJ), 2026)
This study aims to examine the effects of work stress, work discipline, and compensation on the driving safety of Transjakarta bus drivers, with job satisfaction serving as an intervening variable. A quantitative approach with an-explanatory research design was employed. The study involved 125 Transjakarta bus drivers selected through purposive sampling. Data were collected using a structured questionnaire and analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with SmartPLS 4 software. The results indicate that work stress, work discipline, and compensation have positive and significant effects on job satisfaction. Work discipline also has a positive and significant effect on driving safety. However, work stress, compensation, and job satisfaction do not have significant effects on driving safety. Furthermore, job satisfaction does not mediate the relationships between work stress, work discipline, or compensation and driving safety. These findings suggest that work discipline is the most influential factor in improving the driving safety of Transjakarta bus drivers. Therefore, the company should strengthen work discipline by enhancing compliance with Standard Operating Procedures (SOPs), improving supervision, and implementing continuous coaching programs to support safer driving practices.
Keywords: Work Stress; Work Discipline; Compensation; Job Satisfaction; Driving Safety.